Pengaruh Gaya Bahasa Dalam Slogan Iklan di Televisi - H, Henilia (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
One promotional way to attract active users and introduce their products is to create advertising features that include various slogans. Usually advertisements on television use a variety of languages as their promotional strategy and means of publication. However, in reality the public does not fully understand the meaning of various forms of slogan language variations and the function of slogan language variations in advertisements on television. This research aims to describe the language style used in advertising slogans for tea and coffee drinks on television, and the meaning contained in advertising slogans. The research subjects were advertising slogans broadcast on private television channels, namely RCTI, SCTV, INDOSIAR, ANTV, MNC TV, TRANS TV and GLOBAL TV, 2021-2023 edition. The object of research is the language style contained in the advertising slogans for the 2021-2023 edition. Data was obtained from advertising slogans for various products on television in the form of phrases, sentences and images advertising beverage products. This research method is descriptive qualitative. Qualitative methods are research that produces descriptive data, namely in the form of written/spoken words from people or observed behavior. Data collection techniques were carried out using observation techniques and note-taking techniques. The research instrument is a human instrument. Reliability test using intrarater and interrater. Data were analyzed using qualitative descriptive analysis.